Optimization of biodiesel production from stone fruit kernel oil. (February 2019) - Anwar, Mohammad; Rasul, Mohammad; Ashwath, Nanjappa
Abstract: This study investigated the effects of five process parameters, namely methanol: oil molar ratio, catalyst type, catalyst concentration, reaction temperature and reaction time on the transesterification of stone fruit (Prunus armeniaca L.) oil. The physicochemical properties of stone fruit oil and the derived biodiesel were characterized. The stone fruit kernel oil biodiesel was found to satisfy both the ASTM D6751 and EN14214 standards. The optimum process parameters for transesterification of stone fruit kernel oil at an agitation speed of 600 rpm were: methanol: oil molar ratio 6:1; KOH catalyst concentration 0.5 % (of oil weight); reaction temperature 55 °C and reaction time 60 min. The biodiesel yield under these conditions was 95.8 %. These results show that the stone fruit kernel oil will serve as a low-cost feedstock for 2nd generation biodiesel production. This biodiesel can be used in diesel engines without major engine modification.